2018
DOI: 10.1029/2018gl078355
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Networks: A Framework for Studying Multiprocess Multiscale Connectivity Via Coupled‐Network Theory With an Application to River Deltas

Abstract: Transport of water, nutrients, or energy fluxes in many natural or coupled human natural systems occurs along different pathways that often have a wide range of transport timescales and might exchange fluxes with each other dynamically. Although network approaches have been proposed for studying connectivity and transport properties on single-layer networks, theories considering interacting networks are lacking. We present a general framework for transport on multiscale coupled-connectivity systems, via multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Our results show that the presence of directed links results in larger epidemic thresholds with respect to the case of undirected networks, and that the system is more resilient when the interlayer links are directed. Therefore, our conclusions are in line with previous works [20,21] in that directionality is a key topological feature that should not be disregarded as it can lead to new phenomenology and sizable dynamical effects.…”
supporting
confidence: 92%
“…Our results show that the presence of directed links results in larger epidemic thresholds with respect to the case of undirected networks, and that the system is more resilient when the interlayer links are directed. Therefore, our conclusions are in line with previous works [20,21] in that directionality is a key topological feature that should not be disregarded as it can lead to new phenomenology and sizable dynamical effects.…”
supporting
confidence: 92%
“…One important recent innovation in the analysis of nonlinear systems is the use of network representations of system dynamics (Boers et al, 2015;Tejedor et al, 2018;Zhang et al, 2017). Such methods have shown that they are able to capture dynamical properties of continuous dynamical systems, such as the maximal Lyapunov exponent (McCullough et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More complex network representations, such as a multiplex may help in this regard as they allow the representation of a system as a set of multiple networks in which links are allowed within each layer and between layers. This approach has been recently used to represent the transport of fluxes in channels and islands in delta systems (Tejedor et al, 2018).…”
Section: 1029/2019jf005201mentioning
confidence: 99%